Literacy Boost Initiative at SD Muhammadiyah 2 Creative Bontang for Advancing Reading and Writing Competencies : Program Penguatan Literasi Bacaan di SD Muhammadiyah 2 Kreatif Bontang untuk Meningkatkan Kemampuan Membaca dan Menulis - Khatimah, Khusnul; Rahmawati, Yeni; Rachman, Dzul (Journal of Empowerment and Community Service (JECSR), 2023)
Elementary education serves as a crucial foundation in shaping cognitive abilities, comprehension, and the capacity to express ideas both in written and spoken forms. Among the fundamental competencies that need to be instilled early on are reading and writing skills, which are integral components of literacy. This training program is designed to enhance teachers' competencies in developing students' literacy skills through a participatory training approach and intensive mentoring. The training is conducted in the form of a three-day interactive workshop, covering effective reading strategies, creative writing techniques, and the use of both digital and conventional literacy media. The program also emphasizes the importance of fostering a literate and collaborative learning environment, involving teachers, students, and parents in literacy-based learning activities. Success is measured by increased student participation in reading and writing activities, the availability of contextual supplementary reading materials, and the establishment of a simple yet sustainable literacy culture in the classroom. Through this initiative, the goal is to create a strong foundation for lifelong learning and critical thinking among young learners.